Did Household Consumption Become More Volatile? - Gorbachev, Olga (American Economic Review, 2011)
I show that after accounting for predictable variation arising from movements in real interest rates, preferences and income shocks, liquidity constraints and measurement errors, volatility of household consumption in the US increased by 25 percent between 1970 and 2004. The increase was lower than that of volatility of family income. Nonwhite and those with less than 13 years of education, for whom there was no differential increase in income volatility, experienced a significantly larger increase in volatility of household consumption. Substantial differences in wealth and access to credit markets point to the main reason for this divide. JEL: D12, D14, E21, J15